Micromechanical analysis of UD CFRP composite lamina under multiaxial loading with different loading paths. (1st August 2021) - Chen, Jiayun; Wan, Lei; Ismail, Yaser; Hou, Pengfei; Ye, Jianqiao; Yang, Dongmin
Abstract: The influences of loading path on the failure of unidirectional (UD) carbon fibre reinforced polymer (CFRP) composite laminae IM7/8552 are studied. A 3D representative volume element (RVE) based micromechanical model is established using finite element method (FEM) to capture the coupled effects of fibres, matrix and fibre/matrix interface on the failure under different multiaxial loading conditions. An artificial neural network (ANN) is adopted to identify experimentally difficult-to-measure micro-parameters of interface, such as interface thickness and stiffnesses, for the construction of the high-fidelity RVE. In order to precisely control the loading path with the consideration of Poisson's effects, the RVE is loaded by force at the dummy points instead of using the commonly used displacement loading approach. Three different loading paths are compared in each case, and the results show that the failure strength and patterns of the RVE under combined transverse and out-of-plane compressions as well as in-plane shear are independent of loading paths.